The impact of using the Open Class model in developing the communication skills and imagination of the fourth grade students in the social and national education curriculum in Jordan - Al-Tus, Dania Ali Mahmoud; Abu Sneina, Odeh Abdel-Gawad (Journal of Educational and Psychological Sciences, 2018)
The aim of this study was to measure the effect of the use of the open class model in the development of communication skills and imagination among the fourth grade students in the social and national education curriculum in Jordan.The semi-experimental approach of the two groups was used with two pre-test and two tests. The first two tools were developed to measure the development of communication skills and the second to measure the development of visualization skills. Was applied to the sample of the study, which consisted of two randomly selected sections of the fourth grade students at Atekha bint Abd al-Muttalib school in the 2018/2017 academic year. The number of female students in Division (A) included (45) (B) and the number of female students (45) control group.The study found a statistically significant difference between the arithmetical averages of the female students in both groups (experimental and control) on the communication skills development test. Experimental. There was a statistically significant difference between the mean scores of the female students in both groups (experimental and control) on the test of the development of imagination skills, where the experiment obtained a general average (21.78), while the control obtained an average of (21.53). In light of these results, several recommendations have been formulated, the most important of which are the holding of training workshops by educational supervisors to increase attention to teaching models, which contribute to the positive impact in making students the center of the educational process through their active participation in discussion and inquiry and propose solutions and work on using the open class model in teaching education Social, national and other approaches.
Keywords: teaching model; open class; communication; imagination; Social and national education